Turnover of carbon and phosphorus in the microbial biomass depending on phosphorus availability. (October 2017) - Spohn, Marie; Widdig, Meike
Abstract: Adjustment of the mean residence time (MRT) of elements in the soil microbial biomass (SMB) might be an important process by which microbial communities adapt to nutrient-poor environments and maintain their element biomass ratio. Yet, little is known about the turnover of elements such as carbon (C) and phosphorus (P) in the SMB, which is partly due to methodological challenges. This is the first study to determine the MRT of C and P in SMB based on labeling of microbial DNA with 14 C and 33 P. We studied the MRT of C and P in the SMB of topsoil from a temperate, mesic grassland fertilized with five different amounts of P. For this purpose, soil was labeled with 14 C-glucose and 33 P-phosphate and incubated for 24 h, and then, 14 C and 33 P in the soil microbial DNA were determined. The MRT of C and P was calculated based on the C and P content of DNA, and the observation that soil microbial biomass C and microbial DNA are linearly correlated. The SMB-C and the MRT of C in the SMB were not affected by P availability, whereas the microbial community significantly increased the MRT of P in its biomass from 18.1 to 39.0 days with decreasing P availability. Our results indicate that the adjustment of the MRT of individual elements in the SMB is an important process by which microbes adapt to nutrient poor environments and are able to maintain their biomass element ratio when decomposing substrate with a very high C-to-nutrient ratio. Highlights: We determined the mean residence times (MRT) of C and P in the soil microbial biomass (SMB). For this purpose, microbial DNA was labeled with 14 C and 33 P. The MRT of P in the SMB decreased from 39.0 to 18.1 days with increasing P availability. The MRT of C in the SMB did not change with P availability. Increasing the MTR of elements in the SMB allows microbes to maintain their biomass element ratio.